Techno-Economic Study of a Hybrid Solar-Diesel-BESS Power System in Remote Island, Indonesia: Reducing Energy Costs and Carbon Emissions - Umar, Abdullah; Husnayain, Faiz; Rahmat, Ade; Yusmar, Yusmar (Faculty of Engineering, Universitas Tanjungpura, 2025)
The primary goal of this study is to conduct a comprehensive study of the viability of deploying a Photovoltaic-Diesel Hybrid system on Kaleroang Island, Central Sulawesi, Indonesia. The focus of this study is to identify the system configuration that is able to generate the lowest cost of energy and the lowest emissions. Five distinct scenarios are formulated for development. Scenario A encompasses fully diesel generator (DG), scenario B hybrid system DG and photovoltaic (PV), scenario C includes DG integrated with battery storage, scenario D includes DG, PV, and battery configuration, and scenario E includes PV with Battery. A comprehensive techno-economic study was performed to rigorously ascertain which of these system configurations demonstrates the highest competitiveness in terms of cost-effectiveness and operational viability. The results indicate that scenario D, characterized by a net present cost (NPC) of 5,460,903, exhibits a levelized cost of energy (LCOE) of 0.264/kWh, the lowest among the other scenarios. This configuration has been demonstrated to reduce fuel usage, thereby decreasing CO2 emissions by 32.9%. Furthermore, to ensure optimal results, it is imperative to calibrate the PV tilt angle within the range of 3Ëš to 6Ëš, with the orientation of the PV facing north.